Analysis Of The Influence Of Price, Quality Of Service, Halal Label And Location On Coffee Purchasing Decisions At Warkop Binaraga - Intan Fadia; Bayu Eko Broto; Praida Hansyah (International Journal of Economic Research and Financial Accounting, 2025)
This article is entitled "Analysis of the Influence of Price, Service Quality, Halal Label and Location on Purchasing Decisions and Coffee Sales Targets at Kopi Warkop Binaraga." This research was conducted by Intan Fadia as part of her final assignment to obtain a Bachelor of Economics degree in the Management Study Program, Faculty of Economics and Business, Labuhanbatu University. In an era of increasingly tight competition in the coffee industry, understanding the factors that influence consumer purchasing decisions is very important. This study aims to explore the influence of price, service quality, halal label, and location on coffee purchasing decisions at Warkop Binaraga. The proposed hypothesis includes the assumption that each of these factors has a positive effect on purchasing decisions, as well as the simultaneous influence between all variables on purchasing decisions.The research method used is descriptive with an explanatory survey approach, which allows researchers to understand the relationship between variables in a quantitative context. The research population consists of consumers who visit Warkop Binaraga within a certain period, with a sampling technique using simple random sampling or purposive sampling to select relevant respondents. Data were collected through a questionnaire that included questions about price, service quality, halal label, location, and purchasing decisions. Regression analysis is used to test the hypothesis and see the effect of each variable on purchasing decisions. The results of this study are expected to provide in-depth insights for Warkop Binaraga owners and other business actors in formulating more effective marketing strategies. By understanding the factors that influence purchasing decisions, it is expected to increase customer satisfaction and achieve the desired sales target. This study also contributes to the existing literature on consumer behavior in the coffee industry, as well as providing recommendations for further research.Overall, this article emphasizes the importance of a comprehensive analysis of the various factors that influence purchasing decisions, which not only focus on the taste of the product, but also on other elements that can increase the attractiveness and selling value of coffee products in a competitive market.